Effect of Different Nutrient Solutions on Growth, Yield, and Quality of Hydroponic Capsicum Varieties - Rahman, Jahedur; Chandni, Chand Sultana; Ali, Shahajahan; Raihan, Abu; Hossain, M Mokbul (European Journal of Applied Sciences, 2023)
Nutrient solution and its composition may have the effect of growth and yield of capsicum varieties. Individual crop has its specific nutrition requirement for its proper growth in soilless culture. Therefore, it is important to identify specific nutritional composition in capsicum / sweet pepper varieties in Bangladesh. In this study, growth and yield parameter in different varieties of sweet pepper by applying different nutrient solution formulations were investigated. Four levels of nutrient solution concentrations, viz., S1: Full strength Hoagland and Arnon (1940) nutrient solution, S2: ¾ strength Hoagland and Arnon (1940) nutrient solution, S3: Full strength Rahman and Inden (2012) nutrient solution and S4: ¾ strength Rahman and Inden (2012) nutrient solution and four varieties of capsicum, viz., V1: California Wonder, V2: Wonder Bell, V3: Capsicum F1 and V4: Capsicum F1 were treated as treatments. Vegetative growth, physiological, yield contributing characters and antioxidant content were measured. In case of nutrient solution, the highest plant height (119cm), number of fruit per plant (20), individual fruit weight (210g) and fruits yield (3.99 kg/plant) were found highest when S3 nutrient formulation was applied. But statistically similar results were found in S4 V4 which was similar to that of S3. While the ascorbic acid (205.8 mg/100g FW), leaf area (136.8 cm2), leaf mass ratio (0.97g.g-1) and net assimilation rate (0.000012 g.cm-2.d-1) were maximum in S4. In varieties, the highest plant height (119cm), number of fruit per plant (20), individual fruit weight (210g) and fruits yield (3.99 kg/plant) were found in V4 which was similar to that of V3. The highest plant height number of fruits/plant, individual fruit weight, yield/plant were found in S3V3 which was similar to S4V4. Therefore, ¾ strength Rahman and Inden, (2012) nutrient solution can be used for sweet pepper cv. California Wonder in hydroponic system in Bangladesh.